The treatment of total heart block by implantable pacemaker - Aytaç, Aydın (The Turkish Journal of Pediatrics, 1963)
An implantable pacemaker was first used by Chardack on April 18, 1960. The first such operation in Turkey was performed on December 4, 1962, at Hacettepe Medical Center. This paper presents the history and physiopathology of this case, as well as the general clinical application and electro-dynamics of the pacemaker. The writer believes it is essential to have an implantable pacemaker available whenever open heart surgery is done, in order to overcome the common complications of surgical heart block.